The “Chic young men” on the roof: press, urban order, and the newspapers’ pact of silence on the private universe of the elites – São João Del-Rei-MG, 1917 (Ágora Journal, 2022)
This paper analyzes how the press in the city of São João del-Rei dealt with the deviant behavior of members of the local elites. The defense and promotion of a disciplinary urban order had been in progress, in Brazil, since the 19th Century. The analysis of a case involving the transgression of an agreement between the elites and the local press, therefore, it is part of the perspective of Micro-History. The case was the attempt to destroy the periodical A Nota by young men of the important families after the periodical having exposed their names in articles in this newspaper. By examining the circumstances and consequences of the breach of a pact between the authorities, the leaves and the families of the elites are revealed to spare certain names without leaving aside the disciplinary effort. This proves the existence of specific strategies to control each social class.
Keywords: Press; Elites; São João Del-Rei